2015
DOI: 10.2139/ssrn.2611235
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of China's Financial Reform The Efficiency of China's Domestic Banks

Abstract: This paper estimates the cost and pro…t e¢ ciency of Chinese domestic banking sector to evaluate the e¤ectiveness of China's …nancial reforms since 1978. We use the performance of foreign banks as the benchmark because foreign banks, subject to intensive worldwide competition, are perceived as possessing superior governing structure and organization, more advanced technologies and better trained labor force. On the other hand, competition in China's banking sector is mainly in the form of nonprice measures, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Once the role of financial institutions for economic activities has been recognized, the level of bank competition/concentration becomes relevant for many reasons. First, it can influence banks’ efficiency, the product quality and the extent of invention/innovation [ 4 9 ]. Second, the linkage between bank concentration/competition and economic stability is also relevant to financial institutions [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Once the role of financial institutions for economic activities has been recognized, the level of bank competition/concentration becomes relevant for many reasons. First, it can influence banks’ efficiency, the product quality and the extent of invention/innovation [ 4 9 ]. Second, the linkage between bank concentration/competition and economic stability is also relevant to financial institutions [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese economy has witnessed a rapid change due to the anti-corruption movements in the country that undermines the government's role in the real economy. The government has initiated the financial liberalization since 1980s (Hsiao et al, 2015), e.g. the set-up of the big four commercial banks, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we provide novel evidence on the regulatory reform on the bank efficiency using the loan level data. Hsiao et al (2015) shows the impact of the financial reform by evaluating the efficiency of Chinese banks, while they employ bank level data during 2007-2012. Secondly, we point to the impact of corporate governance of borrowing firms on the efficiency of banks.…”
Section: Introductionmentioning
confidence: 99%
“…The reforms of banking sector are widely regarded to be positive. For example,,Hsiao et al (2015),Qian et al (2015) andDong et al (2016) studied China's banking sector from the perspective of cost and profitability, credit rating, professionalism of staff, and concluded that the reform of China's banking industry has achieved a huge success.…”
mentioning
confidence: 99%